Influence of heat treatment on nanocrystalline zirconia powder and plasma-sprayed thermal barrier coatings - 蒋显亮 刘纯波 刘敏 朱晖朝 (Transactions of Nonferrous Metals Society of China, 2010)
Nanostructured zirconia top coat was deposited by air plasma spray and NiCoCrAlTaY bond coat was deposited on Ni substrate by low pressure plasma spray.Nanostructured and conventional thermal barrier coatings were heat-treated at temperature varying from 1050 to 1 250oC for 2-20 h.The results show that obvious grain growth was found in both nanostructured and conventional thermal barrier coatings（TBCs）after high temperature heat treatment.Monoclinic/tetragonal phases were transformed into cubic phase in the agglomerated nano-powder after calcination.The cubic phase content increased with increasing calcination temperature.Calcination of the powder made the yttria distributed on the surface of the nanocrystalline particles dissolve in zirconia when grains grew.Different from the phase constituent of the as-sprayed conventional TBC which consisted of diffusionlesstransformed tetragonal,the as-sprayed nanostructured TBC consisted of cubic phase.